2023
DOI: 10.1021/acs.joc.3c00313
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkylation of Amines by C1–C10 Aliphatic Alcohols Using A Well-Defined Ru(II)-Catalyst. A Metal–Ligand Cooperative Approach

Abstract: A Ru(II)-catalyzed efficient and selective N-alkylation of amines by C1–C10 aliphatic alcohols is reported. The catalyst [Ru(L1a)(PPh3)Cl2] (1a) bearing a tridentate redox-active azo-aromatic pincer, 2-((4-chlorophenyl)diazenyl)-1,10-phenanthroline (L 1a ) is air-stable, easy to prepare, and showed wide functional group tolerance requiring only 1.0 mol % (for N-methylation and N-ethylation) and 0.1 mol % of catalyst loading for N-alkylation with C3–C10 alcohols. A wide array of N-methylated, N-ethylated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 106 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…In our previous work we observed that catalyst 1a efficiently dehydrogenates alcohols to the corresponding carbonyls . The hydrogen removed during the dehydrogenation step remains stored in the azo-chromophore of ligand L 1a , which readily gets transferred to molecular oxygen under air to H 2 O 2 while it reduces a hydrogen acceptor under an inert atmosphere .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In our previous work we observed that catalyst 1a efficiently dehydrogenates alcohols to the corresponding carbonyls . The hydrogen removed during the dehydrogenation step remains stored in the azo-chromophore of ligand L 1a , which readily gets transferred to molecular oxygen under air to H 2 O 2 while it reduces a hydrogen acceptor under an inert atmosphere .…”
Section: Resultsmentioning
confidence: 96%
“… , This was further strengthened by the fact that the 1a -catalyzed dehydrogenation of alcohols remains unaffected in the presence of TEMPO (Scheme , entry 3). However, after repeated efforts, we failed to identify any Ru–H intermediate; instead, the reaction mixture obtained after the stoichiometric reaction of 1a with CH 3 OH showed characteristic −NH stretching frequencies at 2955 and 2915 cm –1 upon IR spectroscopic analysis. , The stoichiometric reaction of 1a with CD 3 OD showed characteristic −ND stretching at 2284 and 2210 cm –1 , indicating the formation of a hydrazo-type intermediate in the reaction mixture (see SI, Figure S1). , Similar formation of a hydrazo-type intermediate was observed during 1a -catalyzed N -alkylation of amines and synthesis of pyrroles .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations